Community medicine: Desperate times calling for desperate measures - Shailendra Singh Chaudhary; Manisha M Nagargoje (Wolters Kluwer Medknow Publications, 2016)
This article is an attempt by authors to find the solutions for some of the common queries and problems faced by postgraduate students and young faculty members of department of Community Medicine. Topics which are discussed here include: nomenclature of the department, teaching and training of undergraduate and postgraduate students, services to the community and job opportunity after completion of degree/diploma in Community Medicine/PSM/Public Health.